Autologous dendritic cells pulsed with allogeneic tumour cell lysate induce tumour-reactive T-cell responses in patients with pancreatic cancer: A phase I study. (July 2022) - Lau, S.P.; Klaase, L.; Vink, M.; Dumas, J.; Bezemer, K.; van Krimpen, A.; van der Breggen, R.; Wismans, L.V.; Doukas, M.; de Koning, W.; Stubbs, A.P.; Mustafa, D.A.M.; et al.
Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is notorious for its poor prognosis even after curative resection. Responses to immunotherapy are rare and related to inadequate T-cell priming. We previously demonstrated the potency of allogeneic lysate-dendritic cell (DC) vaccination in a preclinical model. Here we translate this concept to patients. Methods: In this phase I study, patients with resected PDAC were included when they demonstrated no radiologic signs of recurrence after standard-of-care treatment. Allogeneic tumour lysate-loaded autologous monocyte-derived DCs were injected at weeks 0, 2, 4 and at months 3 and 6. Objectives are feasibility, safety and immunogenicity of allogeneic tumour-DCs. The presence of tumour antigens shared between the vaccine and patient tumours was investigated. Immunological analyses were performed on peripheral blood, skin and tumour. Results: Ten patients were included. DC production and administration were successful. All patients experienced a grade 1 injection-site and infusion-related reaction. Two patients experienced a grade 2 fever and 1 patient experienced a grade 3 dyspnoea. No vaccine-related serious adverse events were observed. Shared tumour antigens were found between the vaccine and patient tumours. All evaluated patients displayed a vaccine-induced response indicated by increased frequencies of Ki67+ and activated PD-1+ circulating T-cells. In addition, treatment-induced T-cell reactivity to autologous tumour of study patients was detected. Seven out of ten patients have not experienced disease recurrence or progression at a median follow-up of 25 months (15–32 months). Conclusion: Allogeneic tumour lysate-DC treatment is feasible, safe and induces immune reactivity to PDAC expressed antigens. Highlights: Pancreatic cancer is an immune-deserted tumour and responses to immunotherapy are rare. Allogeneic-tumour lysate-dendritic cell vaccination is feasible and safe in patients with pancreatic cancer. Dendritic cell vaccination was immunogenic and demonstrated T-cell activation after therapy. Therapy-induced cross-reactive T-cell responses against autologous tumour were found.